'Almost everything else goes to the wayside': Experiences of caseworkers, middle managers and leaders responding to child fatality and near fatality cases. (18th April 2022) - Garcia, Antonio R.; Ibekwe‐Okafor, Nneka; Wasch, Sarah
Abstract: While child welfare scholars and caseworkers have acquired a better understanding of risk factors associated with occurrences of child fatalities due to maltreatment over the past 20 years, little is known about the organisational and system‐level characteristics that impact efforts to prevent or intervene in these cases. As part of a collaborative agreement between a university‐affiliated centre and a state child welfare agency, we conducted interviews by phone with 19 case managers, middle managers and regional leaders who were assigned to manage or oversee a near fatality or fatality case. They illuminated five major themes: 1) their perceived stressors and sources of support; 2) client and perpetrator risk factors; 3) system‐level risk and protective factors; 4) case descriptions; and 5) lessons learned. Relying upon their lived experiences, we offer practice and policy recommendations to Child Abuse Review to support their efforts to prevent and respond to child fatality cases. Efforts should be devoted to evaluating strategies to reduce risk for all families before the child welfare system is involved, supporting workers when they are assigned to fatality cases by reducing caseloads and preparing them for the fatality review process, and embracing a culture of collaboration across and within child‐serving systems. Key Practitioner Messages: To respond effectively to child fatality and near fatality cases, child welfare caseworkers and leaders should be assigned fewer cases in the interim, and receive guidance, consultation, and time to prepare for the fatality review process. Embracing a culture of collaboration across and within child‐serving systems may also prevent fatalities and facilitate an efficient investigative process if/when they do occur.